Environmental function of the land ownership - Vučković, Milica D (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Subject of this research is the environmental function of land ownership, materialised in two civil law institutes. These are sui generis easements of common law and propter rem obligations of french law. Those institutes are a sintesis of different, more or less sincere strivings to give contributions to the Environmental Law from all of the fields of law studies. At the same time, civil law institutes attest to the great evolutive potentials of Civil Law, despite it being so old branch of law.